2007
DOI: 10.11606/issn.1678-4456.bjvras.2007.26658
|View full text |Cite
|
Sign up to set email alerts
|

Morfogênese do testículo de embriões e fetos de vacas da raça nelore (Bos taurus indicus)

Abstract: Este estudo teve como objetivo acompanhar o processo de desenvolvimento testicular desde a fase indiferenciada até sua completa formação. Embriões e fetos de vacas da raça nelore (Bos taurus indicus) foram obtidos em frigoríficos próximos à cidade de Uberlândia, Minas Gerais. As gônadas dos fetos e os embriões foram fixados em bouin e processados para microscópica óptica convencional. A gônada foi observada primeiramente em um embrião de 1,0 cm de comprimento. Em embriões com 2,5 cm a presença da albugínea per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…In this work, the germ cells were in the seminiferous tubules, and large cells with lightly stained, rounded nuclei, as previously reported (JACOMINI et al, 2007), are formed from 31 days of gestation (WROBEL; SUB, 1998). It was observed that after the fifth month of pregnancy, the number of these cells increased according to age (p<0.0001; Figure 1).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…In this work, the germ cells were in the seminiferous tubules, and large cells with lightly stained, rounded nuclei, as previously reported (JACOMINI et al, 2007), are formed from 31 days of gestation (WROBEL; SUB, 1998). It was observed that after the fifth month of pregnancy, the number of these cells increased according to age (p<0.0001; Figure 1).…”
Section: Resultssupporting
confidence: 72%
“…This number increases to 1.5 billion by 10 years of age and is estimated at 3.7 billion cells in human adults (CORTES et al, 1987). During pregnancy, some variation in the number of Sertoli cells in the testes of Nellore bovine fetuses was described (JACOMINI et al, 2007). The Sertoli cells are the first somatic cells to differentiate in the male gonad, and they act as central regulators of testis organogenesis (SVINGEN; KOOPMAN, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations